2007
DOI: 10.1091/mbc.e07-02-0147
|View full text |Cite
|
Sign up to set email alerts
|

A Developmentally Regulated Chaperone Complex for the Endoplasmic Reticulum of Male Haploid Germ Cells

Abstract: Glycoprotein folding is mediated by lectin-like chaperones and protein disulfide isomerases (PDIs) in the endoplasmic reticulum. Calnexin and the PDI homologue ERp57 work together to help fold nascent polypeptides with glycans located toward the N-terminus of a protein, whereas PDI and BiP may engage proteins that lack glycans or have sugars toward the C-terminus. In this study, we show that the PDI homologue PDILT is expressed exclusively in postmeiotic male germ cells, in contrast to the ubiquitous expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 58 publications
(79 reference statements)
5
38
0
1
Order By: Relevance
“…S1 A and B). PDILT was specifically detected in testis, consistent with previous observations in rat and human (23,24). In developing mouse testes, whereas PDIA3 (ERP57) was continuously detected throughout development, PDILT was not detectable until the mice became 3 wk old, indicating postmeiotic expression.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…S1 A and B). PDILT was specifically detected in testis, consistent with previous observations in rat and human (23,24). In developing mouse testes, whereas PDIA3 (ERP57) was continuously detected throughout development, PDILT was not detectable until the mice became 3 wk old, indicating postmeiotic expression.…”
Section: Resultssupporting
confidence: 90%
“…1 A and B), because CLGN-and CALR3-deficient mice had infertile phenotypes attributed to failures in ADAM1/ADAM2 heterodimerization and ADAM3 maturation, respectively (11). PDILT interacted with neither CANX nor CALR, but did bind to CLGN in wild-type mice, consistent with the data from rat (23). We further showed that PDILT interacted with CALR3 and that the signal was stronger than with CLGN (Fig.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Recently, a testis-specific homolog of protein-disulfide isomerase (PDILT) was reported (39,40). Because ubiquitously expressed protein-disulfide isomerases such as ERp57 cooperate together with ER lectin chaperones and help in protein disulfide bond formation (41), it is possible that CALR3 cooperates with PDILT or with other protein-disulfide isomerases during quality control in testes.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of EREcontaining DNA to the oestrogen receptor was recently reported to be enhanced by PDI, independent of its isomerase activity, as evidenced by the ability of the -CGHC-sitedirected mutants to also promote binding (58). Also, PDILT, a PDI homolog, without a redox-active -CGHC-, was shown to display chaperone activity, when found to interact with somatostatin (59). In these examples, the activity of the thioredoxin domains is not required and the chaperone activity is independent of the redox environment.…”
Section: Pdi: Redox-independent Chaperone Activitymentioning
confidence: 99%